Storage of Sputum in Cetylpyridinium Chloride, OMNIgene.SPUTUM, and Ethanol Is Compatible with Molecular Tuberculosis Diagnostic Testing - AFFOLABI, DISSOU (My University, 2019)
Abstract We compared cetylpyridinium chloride (CPC), ethanol (ETOH), and OMNIgene.SPUTUM (OMNI) for 28-day storage of sputum at ambient temperature before molecular tuberculosis diagnostics. Three sputum samples were collected from each of 133 smear-positive tuberculosis (TB) patients (399 sputum samples). Each patient's sputum was stored with either CPC, ETOH, or OMNI for 28 days at ambient temperature, with subsequent rpoB amplification targeting a short fragment (81 bp, GeneXpert MTB/RIF [Xpert]) or a long fragment (1,764 bp, in-house nested PCR). For 36 patients, Xpert was also performed at baseline on all 108 fresh sputum samples. After the 28-day storage (D28), Xpert positivity did not significantly differ between storage methods. In contrast, higher positivity for rpoB nested PCR was obtained with OMNI (n = 125, 94%) than with ETOH (n = 114, 85.7%; P = 0.001). Smears with scanty acid-fast bacilli (AFB) had lower rpoB PCR positivity with ETOH storage (n = 10, 41.7%) than with CPC (n = 16, 66.7%; difference, 25%; 95% confidence interval [CI], 3.5 to 46.5; P = 0.031) or OMNI (n = 16, 69.6%; difference, 26.1%; 95% CI, 3.8 to 48.4; P = 0.031), with no difference between CPC and OMNI. Poststorage, the threshold cycle (CT ) values significantly decreased compared to those prestorage with ETOH (difference, -1.1; 95% CI, -1.6 to -0.6; P = 0.0001) but not with CPC (P = 0.915) or OMNI (P = 0.33). For one patient's ETOH- and CPC-stored specimens with a CT of <10, Xpert gave results of rifampin false resistant at D28, which was resolved by repeating Xpert on a 1/100 diluted specimen. In conclusion, 28-day storage of sputum in OMNI, CPC, or ETOH at ambient temperature does not impact short-fragment PCR (Xpert), including for low smear grades. However, for long-fragment PCR, ETOH yielded a lower PCR positivity for low smear grades, while the performance of OMNI and CPC was excellent for all smear grades. (The study has been registered at ClinicalTrials.gov under registration number NCT02744469.)
Keywords: AFB scanty; OMNIgene.SPUTUM; Xpert; cetylpyridinium chloride; ethanol; isolate; molecular tests; short/long-fragment PCR; sputum; storage